Aperiodically ordered nano-graphene on the quasicrystalline substrate. (18th September 2020) - Maniraj, M; Lyu, L; Mousavion, S; Becker, S; Emmerich, S; Jungkenn, D; Schlagel, D L; Lograsso, T A; Barman, S R; Mathias, S; Stadtmüller, B; Aeschlimann, M
Abstract: Designing exotic structures in low dimensions is key in today's quest to tailor novel quantum states in materials with unique symmetries. Particularly intriguing materials in this regard are low dimensional aperiodic structures with non-conventional symmetries that are otherwise forbidden in translation symmetric crystals. In our work, we focus on the link between the structural and electronic properties of aperiodically ordered aromatic molecules on a quasicrystalline surface, which has largely been neglected so far. As an exemplary case, we investigate the self-assembly and the interfacial electronic properties of the nano-graphene-like molecule coronene on the bulk truncated icosahedral (i) Al–Pd–Mn quasicrystalline surface using multiple surface sensitive techniques. We find an aperiodically ordered coronene monolayer (ML) film on the i-Al–Pd–Mn surface that is characterized by the same local motifs of the P1 Penrose tiling model as the bare i-Al–Pd–Mn surface. The electronic valence band structure of the coronene/i-Al–Pd–Mn system is characterized by the pseudogap of thebare i-Al–Pd–Mn, which persists the adsorption of coronene confirming the quasiperiodic nature of the interface. In addition, we find a newly formed interface state of partial molecular character that suggests an at least partial chemical interaction between the molecule and the quasicrystalline surface. We propose that this partial chemical molecule–surface interaction is responsible for imprinting the quasicrystalline order of the surface onto the molecular film.